Crack paths in multiaxial fatigue of C45 steel specimens and correlation of lifetime with the thermal energy dissipation (Fracture and Structural Integrity, 2021)
The work reports the observed fatigue damage of C45 steel specimens tested in a previous work under multiaxial loading conditions and its relationship with the thermal energy dissipation which has been used in the last decades to estimate the uniaxial fatigue behavior of metals. For this purpose, fatigue data relevant to thin-walled samples made of quenched and tempered C45 steel tested under completely reversed combined axial and torsional cyclic loadings with different biaxiality ratios and phase-shift angles have been analysed. The analyses of crack paths at the initiation point of failure were performed after a 50% stiffness loss that corresponded to a crack size ranging from 7 to 15 mm; afterwards, the characteristic crack paths of each loading condition were analysed by using a digital microscope to identify the orientation of the crack initiation plane. After having broken all fatigue tested specimens under static tensile loading, the fracture surfaces were inspected close to the crack initiation point using a digital microscope. Despite the stress states and fatigue damage mechanisms dependent on the load condition, the Q parameter applied to the present experimental results proved to correlate all multiaxial fatigue test results in a single fatigue scatter band.
Keywords: multiaxial fatigue damage; crack paths; energy method; specific heat loss.